BUDGETARY PROCEDURE AS A MEANS OF ADMINISTRATIVE CONTROL. - Theiss, E. L. (The Accounting Review, 1932)
Abstract Accountancy instruction has to a large extent followed the lines of accounting practice and accounting practice has in general adjusted itself to changes in business practice, although at times this adjustment was made with hesitation and reluctance on the part of some accountants. During the past fifteen years, however, accountants, both public and private, have shown a larger willingness to render a more varied and more valuable service to clients and employers along the lines of interpreting the accounts. Realizing that accounting services were being extended beyond the function of recording into the field of accounting analysis and interpretation, teachers of accountancy have quite generally bent their instruction in the direction of management. Textbooks now guide students into accountancy through the doorway of business problems, commonly referred to as the balance-sheet and profit and loss statement approach. Therefore, when new methods of control are employed by management, such as fixing standards of accomplishment or forecasting operations in order to direct and coordinate all phases of a business, it is quite proper for teachers of accountancy to take notice of such methods and train future accountants to some degree at least in those problems of management that can not be solved unless the accounting records are intelligently analyzed and interpreted.